Implementasi Pembelajaran Coding dan Artificial Intelligency pada Jenjang Pendidikan Dasar (Prosiding Keislaman dan Sains, 2025)
This research discusses coding and artificial intelligence (AI) learning strategies in elementary education. This problem is in accordance with the plan of the Minister of Primary and Secondary Education, Abdul Mu'ti, who will implement this subject as an elective subject which will be implemented in the 2025/2026 academic year, therefore the researcher wants to study in depth what the implementation of this policy is like. This research uses a qualitative research design with the type of library research. explained that qualitative research is a form of research in which data is obtained from empirical sources. In this context, the data collection technique applied is through literature review. The research instruments used are literature in the form of national and international journals, proceedings, and dissertations that discuss the use of artificial intelligence in the educational curriculum. The research steps were carried out systematically by collecting, processing and concluding data. The results of this study explain that coding and AI learning has begun to be implemented by some schools in Indonesia according to the needs of the educational institution. However, the Minister of Primary and Secondary Education will re-enact coding and AI learning as elective subjects in the 2025/2025 academic year, which will be implemented starting from grade 1 of elementary school.
Keywords: Implementation; Coding and AI; Basic Education